Nature sound for pain, how effective will it be? a literature review - Salsabila, Afifah; Windiarti, Sri Endang; Arwani, Arwani (Media Keperawatan Indonesia, 2024)
Pain is one of the reasons for patients to visit the emergency room and is frequently encountered in primary care, outpatient, and inpatient settings. Nature sounds and music is one of the solutions to ease the intensity of pain. This literature review aimed to observe the results of natural pain intervention studies. The literature search for this literature review used Science Direct, PubMed, and Google Scholar. The criteria for this literature review are articles published in the last 5 years (2020-2024), articles in Indonesian and English in national or internationally renowned journals, and scientific articles. Featured articles are articles that the author can download or open. Finally, 5 articles suitable for analysis were obtained. The results showed that providing natural interventions with or without a combination can reduce patients' pain. Not only does it reduce pain, but the natural sound intervention is also useful in reducing stress, anxiety and pain-related patient and systolic blood pressure and heart rate.